FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI - Davita, Caroline; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to obtain empirical evidence regarding the effect of leverage, firm size, intellectual capital, and working capital turnover on financial performance in manufacturing companies listed in the Indonesia Stock Exchange during the period of 2018-2020. The sample was selected using purposive sampling method and the valid data used in this study found 69 manufacturing companies. The data processing techniques using multiple regression analysis assisted by SPSS software (Statistical Product and Service Solution) version 21. The results of this study showed that firm size and working capital turnover have no significant effect on financial performance. Meanwhile, leverage has negative and significant effect on financial performance and intellectual capital has a positive and significant effect on financial performance. The implication of this study is for the role of the company management to pay attention on the level of leverage used by the company and the role of intellectual capital in increasing the company’s financial performance.